Subarachnoid Hemorrhage of Unknown Origin During Pregnancy: Case Report - Engin Üstün, Yaprak; Üstün, Yusuf; Doğan, Kezban; Ateş, Özkan; Kutlu, Ramazan (Gynecology Obstetrics & Reproductive Medicine, 2007)
Subarachnoid hemorrhage (SAH) is a stroke subtype resulting from leakage of blood. The incidence of SAH during pregnancy varies from 1 to 2 per 10000 pregnancies. The most frequent (%85) cause of SAH is a ruptured cerebral aneurysm. A 39-year-old woman at 33 weeks’ gestation experienced abrupt onset of severe headache, neck stiffness, photophobia, and vomiting and was admitted to the hospital and diagnosed as SAH. On neurological examination, no deficits were apparent. A magnetic resonance imaging showed a subarachnoid hemorrhage. Lumbar puncture was performed and SAH was confirmed. It was decided to proceed with a caesarean section. After cesarean delivery of a healthy infant, the patient immediately underwent cerebral angiography, which was normal. Eight days after the initial cerebral angiography, a second angiography demonstrated a suspicious aneurysm and vasospasm; therefore a third angiography was performed and was found normal. At discharge and at clinical follow-up, our patient was asymptomatic. Patients with significant SAH and negative cerebral angiography findings should be considered for further diagnostic testing including repeat cerebral angiography.